1737a Occupation and copd. (24th April 2018) - Fishwick, David
Abstract : Occupational exposures are able to cause a variety of occupational lung diseases that effect either predominantly the airway or the lung parenchyma. Exposures to agents at work that are able to cause COPD remain globally common, although the evidence supporting each of these is variable. Better evidence is available to support the roles of silica, grain dust, coal and cadmium, for example, as specific causes of occupational COPD, whilst multiple epidemiologic al studies also support the harmful effect of exposures to vapours, gases dusts and fumes. This presentation will summarise the current view of occupational COPD, to include its definition, common causes and it will also include discussion of the uncertainties around occupational COPD. The talk will also include specific mention of the harmful effects of inhaled respiratory crystalline silica, and the continuing global problems associated with silicosis.